2000
DOI: 10.1260/0263092001492822
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Agriculture Tractor Interior Noise

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…The measurement of the generated noise level was conducted on the operator's seat in both tractors with and without cabins during the motion over an agrotechnical surface. The research determined that there is a higher level of noise in a cabinless tractor (94 dB) as opposed to a tractor with a cabin (88 dB) [7].…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of the generated noise level was conducted on the operator's seat in both tractors with and without cabins during the motion over an agrotechnical surface. The research determined that there is a higher level of noise in a cabinless tractor (94 dB) as opposed to a tractor with a cabin (88 dB) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Kankar et al 13 used the complex Morlet wavelet based on minimum Shannon entropy criterion to extract the fault feature and presented a methodology for detection of bearing faults by classifying them using three artificial intelligence techniques where SVM is found to be superior to least vector quantization and self-organising maps. Advances in the field of condition monitoring indicators, signal processing and artificial intelligence techniques have been reported in the review papers by Nie et al, 14 Singh and Al Kazzaz, 15 Peng and Chu, 16 and Jardine et al 17 In addition to the above, there are some studies 18,19 on the cabin noise for tractor and car and it is found that the structure born sound due to gearbox is the most annoying noise and hence it is recommended that efforts should be made to control quality of gearbox on assembly line.…”
Section: Introductionmentioning
confidence: 99%
“…s part of the solutions aimed at improving comfort and safety on board agricultural tractors with cabs, by reducing the driver's exposure to disturbing acoustic waves, traditional passive mitigation methods, which involve the use of sound-absorbing and sound-insulating materials, may be not very effective in controlling lowfrequency components. Within the car cabins and, mostly, the cabs of agricultural machinery, the noise at the driver's ear is characterized by low-and medium-frequency components deriving from sources such as the engine or road-tire interaction [1]. Since the late 1980s, studies on Active Noise Control (ANC) systems, mentioned for the first time in a patent from 1936 [2], for noise mitigation within car cabin have been carried out by Elliot et al [3].…”
mentioning
confidence: 99%